2023
DOI: 10.2147/tcrm.s399218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Efficacy and Safety of Tacrolimus Treatment in Membranous Nephropathy: Results of a Retrospective Study of 182 Patients

Abstract: Purpose Tacrolimus is recommended by KDIGO Clinical Practice Guidelines as an initial therapy for the treatment of membranous nephropathy (MN). However, little is known about the factors that influence response and recurrence of the disease after tacrolimus therapy, and there are limited data regarding the duration of tacrolimus treatment. Here, we present a real-world retrospective cohort study of 182 MN patients treated with tacrolimus, aiming to assess the efficacy and safety of tacrolimus in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Another study reported that TAC and CTX combined with corticosteroids in treatment of MN, both had remission rates > 80%, but only the TAC group experienced relapse 21 . Liang et al reported that 182 patients with TAC showed a cumulative PR or CR of 31, 57, and 75% at 6, 12, and 18 months, with a relapse rate of 36.4% 22 . Ramachandran et al evaluated TAC combined with corticosteroids and found remission rates of 74 and 71% at 6 and 12 months 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that TAC and CTX combined with corticosteroids in treatment of MN, both had remission rates > 80%, but only the TAC group experienced relapse 21 . Liang et al reported that 182 patients with TAC showed a cumulative PR or CR of 31, 57, and 75% at 6, 12, and 18 months, with a relapse rate of 36.4% 22 . Ramachandran et al evaluated TAC combined with corticosteroids and found remission rates of 74 and 71% at 6 and 12 months 23 .…”
Section: Discussionmentioning
confidence: 99%